A Formal Model for Stateful and Variant-rich Automotive Functions - Käßmeyer, Michael; Bazan, Peter; Schurius, Markus; German, Reinhard (Formal Verification for Practicing Engineers (FVPE), 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD7.aforma
Keywords: Dependability Analysis; Fault Tree; Minimal Cut Sets; Multi-Valued Decision Diagram; Product Line Engineering; States

A Model based Difference Approach and Change Impact Rules Language to manage Variability and Change Requests in Safety Critical Automotive Functions . - Käßmeyer, Michael; Soden, Michael (SAE World Congress & Exhibition, Technical Paper, 2016)
Automotive engineering processes are dynamic, iterative and driven by changes. Reasons for changes on development artifacts are manifold, but the result is a new evolution step which may influence all, some, or just a single development artifact. Consequently, research on impact analysis put forth approaches to assess the adverse effects of changes. However, understanding and implementing functional changes and its consequences in the safety domain is often aggravated by dependencies between different types of development artifacts, scattered in various (tool) formats. Safety properties may change depending on the type of a modification. Thereby, connected analyses like fault trees, Failure Modes and Effects Analysis (FMEA), and safety concepts cannot be reused easily if the artifacts on which they are based on are affected by changes. In this paper we suggest a new difference analysis approach which allows a (semi-)automated comparison of safety work products based on models. As a model we understand any formalized data structure with well-defined (abstract) syntax and semantics defined by a metamodel [1]. Moreover, we propose a Safety Change Impact Rules Language (SCIRL) targeted at heterogeneous safety artifacts in a model-based safety framework. SCIRL can access artifacts, which are described by metamodels. Moreover, the language is compliant to the Object Constraint Language (OCL) for queries and constraints [2]. The advantage of SCIRL is to synchronize models in a semi-automated manner or refer to artifacts in the safety lifecycle impacted by a change request.
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD7.amodel

Product Line Fault Tree Analysis by Means of Multi-valued Decision Diagrams - Käßmeyer, Michael; Berndt, Rüdiger; Bazan, Peter; German, Reinhard (Measurement, Modelling and Evaluation of Dependable Computer and Communication Systems. MMB&DFT 2016. Lecture Notes in Computer Science, vol 9629., 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.IMMD7.produc

Toward an MDD-based Analysis of Stateful and Variant-rich Automotive Functions - Käßmeyer, Michael; Berndt, Rüdiger; Bazan, Peter; German, Reinhard (CARS 2016-4th International Workshop on Critical Automotive Applications: Robustness & Safety, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD7.toward_7